2020
DOI: 10.3357/amhp.5504.2020
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Entropy in Simulated Flight with Varying Cognitive Loads

Abstract: INTRODUCTION: This study is conducted to observe the effects of cognitive load on the visual search and attention allocation strategies of pilots. Research on pilots’ visual search strategies can provide valuable information regarding attention distribution and transformation, as well as useful situation awareness (SA) predictions.METHODS: A total of 18 pilots performed flight tasks in a two-condition (high and low cognitive load) within-subject experiment to compare their flight performance and eye movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Further demonstrating that the scanning of information in these AOI’s was reduced at the cost of spending more time fixating on or around the runway, which contributed to the reduction in dwell time percentages in these respective AOIs. These findings echo previous work by Van de Merwe et al ( 64 ), which found that fixation rates on various instruments were related to their problem-relevance; with the runway being of prime importance ( 14 ; 46 ). Interestingly, a study by Babu et al ( 7 ) demonstrated that fighter pilots increased their fixation frequency when task difficulty increased during a longitudinal target tracking task, while Tole et al ( 63 ) found no change in the fixation rate of military pilots associated with turbulence in a landing task.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further demonstrating that the scanning of information in these AOI’s was reduced at the cost of spending more time fixating on or around the runway, which contributed to the reduction in dwell time percentages in these respective AOIs. These findings echo previous work by Van de Merwe et al ( 64 ), which found that fixation rates on various instruments were related to their problem-relevance; with the runway being of prime importance ( 14 ; 46 ). Interestingly, a study by Babu et al ( 7 ) demonstrated that fighter pilots increased their fixation frequency when task difficulty increased during a longitudinal target tracking task, while Tole et al ( 63 ) found no change in the fixation rate of military pilots associated with turbulence in a landing task.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, experienced pilots tend to fixate relevant cockpit gauges for briefer periods of time more frequently compared to novice pilots ( 28 ). Additionally, our fixation rate does correct for the increased time spent completing the landing task during the turbulent conditions, whereas previous studies simply reported the fixation frequency count ( 31 ; 46 ; 61 ). Taken together, our traditional eye movement analysis measures suggest that the allocation of attention in low-time pilots became more biased toward the runway in order to monitor and extract the necessary information needed to land during challenging turbulent flight scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye tracking is nonintrusive and can provide measures such as eye fixation position (or location), duration, pupil dilation, visual scanpath (i.e., the time-order of the eye fixations that occurred on display), saccade, blink, and eyelid closure [19,20,32,[37][38][39], in which eyelid closure slowed as fatigue increased [37,38] and saccadic velocity decreased as fatigue increased after long simulated flights [19,20,32,[37][38][39].…”
Section: Eye Movement Measures and Fatigue Evaluationmentioning
confidence: 99%
“…Eye-tracking technology is used in several fields like medicine [ 17 21 ], surgery [ 22 , 23 ], psychology or aerospace [ 24 ]. This technology relies on a video-based eye tracker which determines gaze direction by measuring the position of the corneal reflection of an infrared light relative to the pupil.…”
Section: Methodsmentioning
confidence: 99%